[AR] Dalalat Maddah (sha-ra-ra) wa Mushtaqqatuha fi al-Hadith al-Nabawi al-Sharif: The Concept of (sha-ra-ra) and its Derivations in the Noble Prophetic Hadith (Afaq Lughawiyyah, 2024)
Ancient and contemporary scholars were interested in topics of semantics to determine the objectives of the discourse, what is noticeable - despite the abundance of works - is the lack of probing studies that include all the topics of semantics. Hence, the researchers chose to trace the connotations of the word “shar ” in the noble Prophet’s hadith, to clarify the lexical, terminological, contextual, and pivotal connotations of the word “shar” and its derivatives in the noble prophetic hadith , in an attempt to identify the thread regulating these connotations The researcher adopted the descriptive analytical approach; to realize these indications, by collecting information from its perspectives, extrapolating it, and analyzing it, in order to reach objective scientific results. The research concluded with several results, including: the occurrence of thirteen contextual indications for the substance “evil” and its derivatives in the random sample chosen from the noble Hadith of the Prophet, including: temptation and the most severe punishment of people, infidels, polytheism, injustice and corruption, harm, calamities, and so on. These indications were embodied in two pivotal indications for this article, namely: spread and intensity.